Superior strength-ductility CoCrNi medium-entropy alloy wire. (May 2020) - Liu, Jun-Peng; Chen, Jin-Xi; Liu, Tian-Wei; Li, Chen; Chen, Yan; Dai, Lan-Hong
Abstract: High strength-ductility is the prerequisite requirement for the widely used steel wires in engineering applications. Traditional strengthening strategies on these wires are suffocated inevitably by strength-ductility trade-off dilemma. Recent emerging medium-entropy alloys (MEAs) usually exhibits excellent ductility but relatively lower strength. In this paper, a novel CoCrNi MEA wire with superior mechanical properties was successfully fabricated by heavily drawing process. The yield strength, ultimate tensile strength and elongation could reach 1.5 GPa, 1.8 GPa and 37.4% at liquid-nitrogen temperature, respectively. In-depth microstructure characterization indicates this superior strength-ductility derives from the synergy of dislocations, high-density twins and clear FCC-HCP phase transition. Graphical abstract: Image, graphical abstract